Building Spiritual Defences: Islamic Teachers' Anti-Bullying Strategies at Minhajut Thalibin High School - Andri Isnaeni; Munawar Rahmat; Saepul Anwar (International Journal of Nusantara Islam, 2026)
Safe spaces in education are mandatory. Safe spaces are needed for conduciveness in the implementation of education. Of course, with a safe space, students can engage more effectively in the learning process. Unfortunately, there are still records in the world of education regarding discriminatory behavior, especially bullying behavior. Based on previous research, spiritual intelligence can influence a person's social competence, moral values, and ethics. However, previous studies have not conducted many studies on how Islamic Religious Education teachers' strategies in developing spiritual intelligence to deal with bullying behavior. This study aims to identify strategies carried out by Islamic Religious Education teachers in developing spiritual intelligence to prevent bullying behavior. This study uses a qualitative approach with case studies. The results of this study show that Islamic Religious Education teachers have an important role with their strategies through role models, habituation, and approaching religious values. in strengthening spiritual intelligence to prevent student bullying behavior.